Surgical treatment of metastatic VIPoma: a case report. (December 2021) - Azizian, Azadeh; König, Alexander; Hartmann, Amelie; Schuppert, Frank; Seif Amir Hosseini, Ali; Kitz, Julia; Ghadimi, Michael
VIPoma, a neuroendocrine tumour mostly occurring in the human pancreas and producing high levels of vasoactive intestinal peptide, is a rare disease that presents with a wide spectrum of symptoms, including intense diarrhoea, hypokalaemia, and cardiac complications, with life-threatening consequences. In most cases, metastatic lesions are present at VIPoma diagnosis. Treatment options include symptomatic therapy, chemotherapy, radiation and surgery. Due to its low incidence, there are no evidence-based therapy recommendations to date. Here, we present a case of a 39-year-old woman with severe symptoms due to VIPoma of the pancreas with diffuse hepatic metastasis, who underwent simultaneous resection of the primary tumour, extensive liver resection and radiofrequency ablation. The patient was released in good health and was recurrence-free during 12 months surveillance. According to the existing literature and our own experience, surgical procedures appear to be the most promising therapy option for cases with diffuse hepatic metastasis, offering patients relief from their symptoms and (chemo)therapy-free time.